1972
DOI: 10.1002/pssa.2210130221
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the stoichiometry and impurity content of thin silicon oxide films using Rutherford scattering of MeV α-particles

Abstract: It is described how the Rutherford scattering of MeV α‐particles may be used to study the stoichiometry and impurity content of thin silicon oxide films. The relative concentrations of silicon to oxygen can be measured to ≈ 5%, and in the most favourable cases, impurity concentrations as low as ≈1018 ions cm−3 can be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The electrical properties of these thin films exhibit widely differing behaviour for apparently identical starting materials and fabrication procedures. In a previous publication (Morgan and Gittins 1972) we showed that Rutherford scattering can be used to characterize thin SiO, films. The energy spectrum for a-particles scattered from an Si/SiOz/Au specimen.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The electrical properties of these thin films exhibit widely differing behaviour for apparently identical starting materials and fabrication procedures. In a previous publication (Morgan and Gittins 1972) we showed that Rutherford scattering can be used to characterize thin SiO, films. The energy spectrum for a-particles scattered from an Si/SiOz/Au specimen.…”
Section: Resultsmentioning
confidence: 98%
“…The removal of the background spectrum has enabled some 12 impurity peaks to become visible without any masking from the background. In the fabrication of this oxide there was no apparent difference from the procedures which have been used consistently to fabricate SiOz (Morgan and Gittins 1972). The origin of the A1 peak is boat contamination.…”
Section: *mentioning
confidence: 97%
See 2 more Smart Citations